2019
DOI: 10.1038/s41467-019-13139-9
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic antibody targeting osteoprotegerin attenuates severe experimental pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a rare but fatal disease. Current treatments increase life expectancy but have limited impact on the progressive pulmonary vascular remodelling that drives PAH. Osteoprotegerin (OPG) is increased within serum and lesions of patients with idiopathic PAH and is a mitogen and migratory stimulus for pulmonary artery smooth muscle cells (PASMCs). Here, we report that the pro-proliferative and migratory phenotype in PASMCs stimulated with OPG is mediated via the Fas receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Furthermore, the authors identified that OPG-mediated proliferation of VSMCs occurred via activation of α v β 3 integrin/FAK/Akt signals, since blocking α v β 3 integrin using siRNA technology in the presence of OPG prevented phosphorylation of FAK and Akt, and VSMC proliferation (51). More recently, OPG's pro-proliferative and pro-migratory effects in VSMCs was found to be mediated via another TNF receptor, Fas (74). Here, the authors established that the physical interaction of OPG with Fas was necessary to activate cell proliferation, migration and survival of pig aortic VSMCs, since neutralising Fas inhibited these processes (74).…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the authors identified that OPG-mediated proliferation of VSMCs occurred via activation of α v β 3 integrin/FAK/Akt signals, since blocking α v β 3 integrin using siRNA technology in the presence of OPG prevented phosphorylation of FAK and Akt, and VSMC proliferation (51). More recently, OPG's pro-proliferative and pro-migratory effects in VSMCs was found to be mediated via another TNF receptor, Fas (74). Here, the authors established that the physical interaction of OPG with Fas was necessary to activate cell proliferation, migration and survival of pig aortic VSMCs, since neutralising Fas inhibited these processes (74).…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…More recently, OPG's pro-proliferative and pro-migratory effects in VSMCs was found to be mediated via another TNF receptor, Fas (74). Here, the authors established that the physical interaction of OPG with Fas was necessary to activate cell proliferation, migration and survival of pig aortic VSMCs, since neutralising Fas inhibited these processes (74). Most significantly, the therapeutic potential of OPG in attenuating established PAH was shown -treatment of mice with a human antibody targeting OPG in multiple models of PAH inhibited pulmonary vascular remodelling and features of PAH (74).…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, our study has provided strong genetic evidence that OPG functions in an HS-dependent manner and established HSPG as an integral component of the OPG/RANKL/RANK pathway. As OPG also plays other biological functions such as inhibiting vascular calcification and promoting pulmonary vascular remodeling, skeletal muscle strength, and liver steatosis (24)(25)(26)(27)(28), it would be interesting to examine whether HS also regulates OPG functions in these systems. The opg AAA mice reported here would certainly be an invaluable tool to better understand the diverse physiological functions of OPG.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the importance of TRAIL in infection, fibrosis and cancer might complicate therapeutic targeting of this pathway. However, other mediators known to interact with TRAIL, such as osteoprotegerin, have shown therapeutic promise (12).…”
Section: Editorial On the Research Topic Pulmonary Hypertension: Mechmentioning
confidence: 99%